Developing an Authentic Project-Based Assessment Model on Sociology Learning of Senior High School Students - Ike Sylvia; Syafri Anwar; Khairani Khairani (International Conferences on Educational, Social Sciences and Technology)
This article aims to describe an authentic project-based assessment model in improving students' Higher Order Thinking Skills (HOTS) on Sociology learning. This study used a mix-method design that applied ADDIE procedural to gain valid and reliable outcomes. Data collection used multiple techniques involving guided-interviews, survey, validity test, item instrument sheet, HOTS multiple questions with students' elicitation and observation sheet. The study results revealed that: (1) A characteristic of the authentic project-based assessment modelrefers toextensive assessments such as performance, attitude, presentation, product, project, and comprehension. Both performance and attitude assessments used during the project assessment. (2) An implementation of the authentic project-based assessment model is valid and reliable after givingan experimental treatmentin the class of X IIS SMAN 1 Padang that related to cognitive, affective and skills area. (3) An authentic project-based assessment model increased students' Higher Order Thinking Skills (HOTS) regarding critical thinking and problem-solving aspects, communication skill aspects, creativity and innovation aspects, and collaboration aspects.